Depth Effect on Lightness Revisited: The Role of Articulation, Proximity and Fields of Illumination. (September 2013) - Radonjić, Ana; Gilchrist, Alan L.
The coplanar ratio principle proposes that when the luminance range in an image is larger than the canonical reflectance range of 30:1, the lightness of a target surface depends on the luminance ratio between that target and its adjacent coplanar neighbor (Gilchrist, 1980 ). This conclusion is based on experiments in which changes in the perceived target depth produced large changes in its perceived lightness without significantly altering the observers' retinal image. Using the same paradigm, we explored how this depth effect on lightness depends on display complexity (articulation), proximity of the target to its highest coplanar luminance and spatial distribution of fields of illumination. Importantly, our experiments allowed us to test differing predictions made by the anchoring theory (Gilchrist et al., 1999 ), the coplanar ratio principle, as well as other models. We report three main findings, generally consistent with anchoring theory predictions: (1) Articulation can substantially increase the depth effect. (2) Target lightness depends not on the adjacent luminance but on the highest coplanar luminance, irrespective of its position relative to the target. (3) When a plane contains multiple fields of illumination, target lightness depends on the highest luminance in its field of illumination, not on the highest coplanar luminance.